Global three-dimensional constituent fields derived from profile data - Douglass, Anne R.; Rood, Richard B.; Stolarski, Richard S.; Schoeberl, Mark R.; Proffitt, Michael H.; Margitan, James J.; Loewenstein, Max; Podolske, James R.; Strahan, Susan E. (1990)
The success of three-dimensional simulations of stratospheric constituent variability depends critically on the initialization of the constituent fields within the global model. This paper describes a technique for generating global three-dimensional fields from vertical constituent proflies. The technique uses potential vorticity (q) and potential temperature (theta) to map the profiles onto the global domain. The profiles used here are obtained from a two-dimensional model calculation that reproduces the relationship between theta, q, N2O and O3 observed during the Airborne Arctic Stratospheric Expedition. The method is verified by comparison with satellite data, aircraft data, and model simulations.